Specificity of DNA binding of the c-Myc/Max and ARNT/ARNT dimers at the CACGTG recognition site. - Swanson, H I (1999)
Basic helix-loop-helix proteins that interact with the DNA recognition site CACGTG include the c-Myc/Max heterodimer and the ARNT (Ahreceptornucleartranslocator) homodimer. We have utilized a PCR-based protocol to identify high affinity binding sites of either the c-Myc/Max or ARNT/ARNT dimers and analyzed the ability of these dimers to interact with their derived consensus sequences and activate genes. chi(2)analysis of the selected DNA recognition sites revealed that DNA binding of the ARNT homodimer is symmetric, resulting in the consensus sequence RTCACGTGAY. Gel shift analysis demonstrated that the flanking nucleotides play an important role in dictating DNA binding affinity of the ARNT homodimer. These flanking sequences also regulate the ability of ARNT to competitively displace the c-Myc/Max heterodimer from a CACGTG-containing sequence. However, transient transfection analyses in CV-1 cells revealed that ARNT and c-Myc/Max exhibited similar abilities to activate transcription through each other's consensus sequences. Taken together, these results indicate that although binding affinity of these dimers for the CACGTG core sequences may be differentially influenced by flanking nucleotides, transcriptional activity may also be determined by other factors, such as cellular concentrations of these proteins and their co-activators.